2022
DOI: 10.35912/jgas.v2i2.1443
|View full text |Cite
|
Sign up to set email alerts
|

Governance challenges and resurgence of Igbo nationalism in Nigeria: Dissecting Indigenous People of Biafra (IPOB)

Godwin Onu,
Amobi P. Chiamogu,
Uchechukwu P. Chiamogu

Abstract: Purpose: The remote and immediate causes of the Nigerian civil war are rather deepening in the psyche of Ndi-Igbo in contemporary Nigerian politics and administration. Amidst the introduction of the Reconciliation, Reconstruction, and Rehabilitation (3Rs) policy over four (4) decades ago, the Ndi-Igbo are not just marginalized but alienated and separated from political power and its benefits in an ethnically and religiously deeply divided federation. More divesting wounds are flagrantly being inflicted upon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Adequate provision of electricity is required to operate polling place (client) voting machines whereas internet connectivity is required for internet (i-voting). In addition, comprehensive biometric data for identification and monitoring election, a basic requisite for e-voting adoption, is lacking (Onu & Chiamogu, 2012). Edokpayi (2015) observed that from the onset, even with the introduction of PVCs and smart card readers, it was clear, from knowledge of hindsight, that some people would seek victory for their parties by any means necessary.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Adequate provision of electricity is required to operate polling place (client) voting machines whereas internet connectivity is required for internet (i-voting). In addition, comprehensive biometric data for identification and monitoring election, a basic requisite for e-voting adoption, is lacking (Onu & Chiamogu, 2012). Edokpayi (2015) observed that from the onset, even with the introduction of PVCs and smart card readers, it was clear, from knowledge of hindsight, that some people would seek victory for their parties by any means necessary.…”
Section: Statement Of the Problemmentioning
confidence: 99%